Pediatric Retroperitoneal Vascular Injuries - Mir, Dr. Mohd. Altaf; Kumar, Prince (Pediatric Abdominopelvic Trauma, 2024)
Pediatric retroperitoneal vascular trauma poses unique challenges in diagnosis and management due to anatomical variations, age-specific injury mechanisms, and limited clinical data. This chapter provides a comprehensive overview of pediatric retroperitoneal vascular trauma, focusing on clinical considerations and management strategies. We discuss the epidemiology, etiology, and pathophysiology of retroperitoneal vascular injuries in the pediatric population, highlighting the importance of early recognition and prompt intervention. Diagnostic modalities, including imaging techniques and adjunctive tools, are reviewed in detail, emphasizing their role in accurate injury assessment and treatment planning. Additionally, we explore the principles of hemodynamic stabilization, surgical approaches, and minimally invasive interventions tailored to pediatric patients with retroperitoneal vascular injuries. By elucidating the nuances of pediatric retroperitoneal vascular trauma, this chapter aims to enhance the understanding and optimize the management of these challenging injuries in pediatric patients.